Anemia Gestacional y su influencia en el parto Pretermino en pacientes atendidas en el Hospital II-2 Minsa Tarapoto. Periodo Julio – Setiembre 2014 - Hidalgo Mozombite, Richard (2014)
In order to determine the relationship between gestational anemia and preterm delivery in Patients treated at the hospital II - 2 Tarapoto. July - September 2014; the methodology Consisted of a descriptive correlational study and cross-section. In the study conducted, The population was made up of 450 patients were treated at the hospital for childbirth, Period July - September 2014 and within 60 patients formed our sample who have some Type of gestational anemia and who delivered preterm and they met our inclusion criteria. For proper processing and data reading statistical Chi square test that allowed determining Whether two variables are associated or not used. In the study, the following results were Obtained: The incidence of gestational anemia is 133.3 X 1000 addressed; and the Incidence of preterm births in anemic pregnant women is 133.3 x 1,000 attended. The Average age of the anemic pregnant women is 26.2 years; most have secondary Education level of 50.0%. They are common law marriage 68.3%. 75.0%; of pregnant Women had mild anemia; 25.0% of pregnant women controlled (≥ 6 CPN) had mild Anemia; and 68.3% of pregnant women had mild anemia had a history of preterm births. Preterm births in pregnant women with mild anemia were mild prematurity 61.7%, 8.3% Moderate prematurity and extreme prematurity 1.7%. In conclusion: There is a highly Significant correlation between gestational anemia and preterm delivery (p <0.01) in Patients treated at Hospital II - 2 MINSA Tarapoto. Period July - September 2014.